2019
DOI: 10.1016/j.sjbs.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted extraction of some branded tea: Optimization based on polyphenol content, antioxidant potential and thermodynamic study

Abstract: Tea is one of the top beverages used around the world every day, which contains a high amount of polyphenols and antioxidants. The main aim of this research is to quantify some marketed black tea (Rabea, Lipton, Alkbous, Green gold and Haritham) for phenolic contents and antioxidant potential evaluation by ultrasound solvent extraction and was compared with conventional extraction. Ultrasonic extraction was optimized by considering frequencies (26 kHz, 40 kHz), temperature (30, 40 and 50 °C), and power (30, 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…GTE showed an inhibition of 71.77%, conferred by the relative amount of catechins and GA [ 82 ]. Afroz Bakht et al [ 83 ] studied the antioxidant activity from DPPH of five commercial teas, finding percentages of inhibition in the 24–71% range. In addition, Lu and Chen [ 84 ] reported percentages of inhibition between 33% and 62%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GTE showed an inhibition of 71.77%, conferred by the relative amount of catechins and GA [ 82 ]. Afroz Bakht et al [ 83 ] studied the antioxidant activity from DPPH of five commercial teas, finding percentages of inhibition in the 24–71% range. In addition, Lu and Chen [ 84 ] reported percentages of inhibition between 33% and 62%.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Lu and Chen [ 84 ] reported percentages of inhibition between 33% and 62%. In this sense, it is important to highlight that antioxidant activity is dependent on the quantity of secondary metabolites that the plant manages to synthesize in its development stage, which is influenced by the variety of the plant, the environmental conditions [ 85 , 86 , 87 ], and the extraction method used [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…The catechin content of the selected green tea types were compared to that of a green tea catechin-based supplement, whereas the diversity in other phenolic, polyphenolic, and non-phenolic compounds was also evaluated. To this purpose, taking into account that ethanol is a good solvent for polyphenol extraction [24], also for higher molecular weight flavanols, alcoholic extracts were prepared by means of ultrasound-assisted maceration [25]. Previous investigation on black tea highlighted that the use of ultrasonic intensification led to an increase in polyphenols by approximately 15% in respect to conventional maceration [26].…”
Section: Chemical Composition Of Alcoholic Extracts From Commercializmentioning
confidence: 99%
“…The propagation of ultrasound waves in a medium generates physical and chemical effects which can be exploited for improving the efficiency of various food processing operations. Thus, the ultrasound technology was explored to enhance the food quality by reducing the process time, energy and increasing shelf life [11,12]. It has been reported that ultrasound energy can be used to increase extraction yields by disrupting cell tissues [12,13].…”
Section: Introductionmentioning
confidence: 99%